1978
DOI: 10.1002/j.1556-6978.1978.tb01072.x
|View full text |Cite
|
Sign up to set email alerts
|

Counselor Trainee Effectiveness: More Puzzle Pieces?

Abstract: This study continues the search for meaningful relationships between counselor trainee characteristics and effectiveness. Self-disclosure, dogmatism, locus of control, Machiavellianism, academic aptitude, and sex of counselor trainees were investigated for their relationships to effectiveness during practicum or internship. The nature of these relationships as well as their implications for the counseling profession are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

1980
1980
1995
1995

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
0
13
1
Order By: Relevance
“…The criterion measure was the trainee's performance during practicum as assessed by the supervisor's ratings on the Counselor Evaluation Rating Scale (CERS). Although their data supported earlier conclusions reported by Rowe, Murphy, and DeCsipkes (1975) regarding the independence of counselor trainee personality characteristics and judgments of their effectiveness, the Loesch et al (1978) article failed to consider another highly important variable; the client's satisfaction with the counseling experience as an index of counseling effectiveness.…”
contrasting
confidence: 48%
See 2 more Smart Citations
“…The criterion measure was the trainee's performance during practicum as assessed by the supervisor's ratings on the Counselor Evaluation Rating Scale (CERS). Although their data supported earlier conclusions reported by Rowe, Murphy, and DeCsipkes (1975) regarding the independence of counselor trainee personality characteristics and judgments of their effectiveness, the Loesch et al (1978) article failed to consider another highly important variable; the client's satisfaction with the counseling experience as an index of counseling effectiveness.…”
contrasting
confidence: 48%
“…One important aspect of this study was its extension of the Loesch et al (1978) study focusing primarily on the interrelationships between counselor trainees, supervisors, and clients. The researchers suggest that the evaluation of training should be made from a number of perspectives (e.g., trainee, supervisor, client, independent judge) and on several dimensions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loesch, Crane, and Rucker (1978) attempted to correlate counselor self-disclosure, dogmatism, locus of control, Machiavellianism, academic aptitude, and sex of counselor trainees with counselor evaluation ratings and concluded that "judgments of some aspects of counselor trainee effectiveness are independent of some counselor trainee personality characteristics" (p. 202). They suggested that programs spend more time on counseling-skills development and evaluation and less time on trainee personality Kathleen Yosr Ritter is a professor of counselor education, School of Educarion, California Slate College, Bakersjeld. characteristics.…”
Section: Personality Characteristics Training Methods and Counselinmentioning
confidence: 99%
“…Even studies that attempted to assess several personality characteristics by traditional means (Loesch et al, 1978) have found inconclusive results. One "isolated" study (in terms of the number of variables assessed) found numerous significant correlations between POI scores and seven measures of counselor behaviors (Selfridge & Vander Kolk, 1976).…”
Section: Personality Characteristics and Counselor Effectivenessmentioning
confidence: 98%